Pengaruh Intensitas Dan Teknik Perlatihan Teater Terhadap Kemampuan Seni Peran Anggota Teater Langit Sidoarjo - Az-Zahra, Amalia Rizka; Parmin, Parmin (TRANSFORMATIKA, 2023)
The background of this research is the low intensity of practicing theater for members of the Sidoarjo Sky Theater and the lack of use of training techniques in their training activities. This makes researchers very enthusiastic to wrap this topic as research. The purpose of this study was to describe the application and effect of adding intensity and training techniques to support the acting abilities of members of the Sky Theater SMAS Wachid Hasyim 2 Taman Sidoarjo. This study uses a quantitative descriptive method and is included in experimental research. The data in this study were taken from the results of field observations, the acquisition of practice scores and members' responses. All data was collected using observation techniques, tests, and questionnaires. The results of this study are; the first is how to apply the intensity and technique of theater training to support the acting skills of members of the Sidoarjo Sky Theater. Second, the effect of adding intensity and training techniques according to the needs or character of the member students. Third, the response of members of the celestial theater after performing a mini performance after going through various exercises with several techniques.